Force majeure [videorecording (DVD)] - Östlund, Ruben, 1974-; Kongsli, Lisa Loven, 1979-; Kuhnke, Johannes Bah; Wettergren, Clara
An idyllic family skiing vacation takes a stunning turn when an avalanche threatens the ski lodge restaurant, sending people fleeing and demanding quick decisions that change the course of the family dynamics and trust.